Glycocalyx Shedding is Enhanced by Age and Correlates with Increased Fluid Requirement in Patients with Major Burns. Issue 1 (July 2018) - Osuka, Akinori; Kusuki, Hirofumi; Yoneda, Kazuhiro; Matsuura, Hiroshi; Matsumoto, Hisatake; Ogura, Hiroshi; Ueyama, Masashi
ABSTRACT: Background: Massive fluid shift after severe burn injury leads to edema and intravascular fluid loss that may result in burn-induced compartment syndrome (BICS) when corrected by aggressive fluid resuscitation. Factors causing this fluid shift remain unclear. Because glycocalyx regulates endothelial permeability, we hypothesized that glycocalyx shedding would increase fluid requirements in burn patients. This prospective cohort study aimed to identify relationships between shedding of the glycocalyx and fluid requirements after burn injury. Methods: Patients aged more than 18 years with burn injury over more than 20% total body surface area (TBSA) were enrolled. Patient background factors including age, sex, burn size, and inhalation injury were recorded at patient enrollment. Serum syndecan-1, known as a biomarker of glycocalyx shedding, was serially measured on admission, day 1, days 3 to 5, around 1 and 2 weeks, and 1 month after the injury to observe postburn injury kinetics of syndecan-1. As biomarkers of endothelial damage, soluble thrombomodulin, antithrombin III, and plasminogen activator inhibitor-1 were also measured. We determined the relationship between syndecan-1 and initial 24-h fluid requirements and between syndecan-1 and morbidity/mortality. Results: We enrolled 39 patients (median age, 55 years; median burn size, 35%TBSA): 16 developed BICS, and 10 patients died. Syndecan-1 level on admission was significantly higher than that in healthy volunteers and remained so. Syndecan-1 level on admission was associated with patient age ( ρ  = 0.50, P  = 0.001) but not burn size ( ρ  = 0.08, P  = 0.63), and antithrombin III level on admission was negatively associated with burn size ( ρ  = −0.48, P  = 0.002). The syndecan-1 level on admission was significantly associated with fluid requirement (mL/kg) ( ρ  = 0.38, P  = 0.017). After adjustment for age, sex, %TBSA, and inhalation injury, syndecan-1 was an independent parameter for the increase in fluid requirement ( P  = 0.04) and development of BICS ( P  = 0.03) by multivariable regression analysis. These findings suggested that glycocalyx shedding increased in an age-dependent manner, whereas antithrombin III decreased according to burn size. Conclusions: Glycocalyx shedding occurs soon after burn injury in an age-dependent manner. To reduce fluid-related complications such as BICS, new strategies to protect glycocalyx in burn patients are needed.